Desenvolvimento e validação de instrumento de suporte à orientação farmacêutica para dispensação de medicamentos prescritos - Rocha, Kérilin Stancine Santos (2018)
Introduction. Dispensing is fundamental in patient care, since pharmaceutical counseling enables patients to receive and understand the information necessary to use medicines correctly. Although pharmaceutical counseling is a quality indicator on drug dispensing, in Brazil, protocols to guide pharmacists on this practice are scarce. Thus, research is necessary for the development and validation of instruments to support pharmaceutical counseling on dispensing prescription medicines. Objective. To develop and validate an instrument to guide pharmaceutical counseling for dispensing prescription medicines. Methods. A methodological development study was carried out from February 2017 to October 2017. The development of the instrument included the following steps: (1) elaboration of the prototype based on a previous systematic review; (2) brainstorming meeting with pharmacists, and (3) pre-Delphi. Then, the content validation of the instrument was carried out with the Delphi technique. Forty Brazilian pharmacists specialized in Dispensing were invited. They were instructed to judge the instrument, according to previously established criteria. At the end of the judgment rounds, the content validation index (CVI) was calculated. The items were considered validated if the CVI> 0.80. The present study was approved by the Ethics Committee of the Federal University of Sergipe. Results. The stages that comprised the development generated three versions of the instrument: prototype; version 1 (modified instrument after brainstorming) and version 2 (instrument modified after pre-Delphi). Version 2 of the instrument was submitted to the content validation process, in which 29 pharmacists (return rate 72,5%) made the judgment in the first round and 23 pharmacists (return rate 79,31%) in the second round. All items obtained CVI higher than 0.82 and were considered validated. Thus, the final instrument comprised three components: suggestions of questions; reasoning of the Dispensing process; and suggestions of counseling and other behaviors, being composed of 11 steps, in which each step represents a stage of clinical reasoning. Conclusion. The instrument to support pharmaceutical counseling on dispensing prescription medicines, developed based on a systematic review and validated using the Delphi technique, presents the main counseling that must be realized during that service. Thus, this instrument could support pharmacists and create referential to improve Dispensing in Brazil, in line with developed countries.